The Chemical and Physico-Chemical Properties of Sorghum Starch and Flour - Hathaichanok Chanapamokkhot; Masubon Thongngam (Agriculture and Natural Resources, 2007)
The chemical and physico-chemical properties of starch and flour from sorghum (KU 439 and KU 804) were determined and then these properties were compared with those of starch and wheat flour for alternative replacement. Protein content in sorghum flour from cultivar KU 439 (439F) and KU 804 (804F) were 6.28 and 9.47% respectively, which were lower than those of hard (HWF) and soft wheat flour (SWF) (14.89 and 11.24% respectively). So the starch or flour from sorghum can be used to replace wheat in gluten-free products. Amylose content of sorghum starch (439S and 804S) and wheat starches (HWS and SWS) were 27.18, 25.35, 28.06 and 23.45% respectively. Swelling power (SP) of sorghum and wheat starch were increasing with temperatures. At temperature above 75°C, the SP of sorghum starch became higher than that of wheat starch. Having compared the pasting properties of starch, it was found that the pasting temperature of HWS was higher than that of 804S, 439S and SWS (p<0.05). On the other hand, peak viscosity and breakdown of sorghum of the 439S and 804S were higher than those of wheat starch; while the final viscosity and setback of 439S and 804S were lower. Furthermore, the pasting properties of flour had shown that peak viscosity, final viscosity and setback of 439F and 804F were higher than HWF and SWF; while breakdown value of 439F, 804F and SWF were lower than HWF (p<0.05).